Nutritional Value Assessment of Marasmiellus inoderma Sporophores Cultivated on Maize Cobs and Coffee Grounds - Mbumbu Luswamu Gertrude; Tshisuaka Nkongolo Alain; Dibaluka Nlandu Carmelle; Monizi Mawunu; Iteku Bekomo Jeff; Lumande Kasali Joseph; Mundele Mukongo Justin; Koto-Te-Nyiwa Ngbolua; Dibaluka Mpulusu Simon; Lukoki Luyeye Félicien (Biology, Medicine, & Natural Product Chemistry, 2025)
The Democratic Republic of Congo possesses significant agricultural potential, yet its population faces food insecurity, malnutrition, and limited access to essential foodstuffs, resulting in famines in several provinces. This study conducted a comparative analysis of yields and protein content in Marasmiellus inoderma sporophores cultivated on maize cobs and coffee grounds, as well as those collected from the wild. Experiments were carried out at four sites: the Luki Biosphere Reserve (Kongo Central), the experimental garden, the soil laboratory, and the myciculture laboratory. Average yields after four flushes were 31.7 % on maize cobs and 28.23 % on coffee grounds. Protein content was higher in sporophores cultivated on maize cobs (29.37 %) than on coffee grounds (24.98 %), with laboratory-grown samples consistently exhibiting greater protein levels than wild-collected sporophores. These results indicate that cultivating M. inoderma on locally available agro-industrial substrates offers a promising strategy to enhance food security and reduce malnutrition in the DRC, with strong potential for dissemination among both urban and rural producers.